Process of Large Vehicle Driver Admission - Ahmad Sutrian; Syamsurizal (Lead Journal of Economy and Administration, 2022)
The purpose of this study is to find out how the process of accepting large vehicle drivers is, to find out the obstacles in the process of accepting large vehicle drivers and to find solutions to the problems of the large vehicle driver acceptance process. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the process of accepting large vehicle drivers. In this study, data relating to the author's study are sourced from library studies, field studies, and documentation techniques. The results of the study of the Large Vehicle Driver Acceptance Process are as follows: the company has carried out a large vehicle driver acceptance process through several stages starting from filling out the driver acceptance form and interviewing the HRD section, health checks at the clinic, conducting driver tests, participating in devensive driving training, and finally HRD decides whether to accept the driver candidate or not. Constraints experienced by the company in the process of accepting drivers of large vehicles caused by the unavailability of a special room for psychological tests and tests of knowledge of traffic signs. The next obstacle is the limited source of doctors to operate in the company which results in the length of treatment for patients or prospective drivers who will take a health test, besides that there are obstacles in the occupational health and safety division, namely the working computer facilities for devensive driving training which are very minimal. The solution taken by the company from the above constraints is that the company will create a special room for test activities carried out by the HRD section in conducting a new driver acceptance test and adding medical experts, and the company must add a computer or laptop device.